DINAMIKA POPULASI SUMBER DAYA IKAN LAYUR (Lepturacanthus savala) DI PERAIRAN SELAT SUNDA (Population Dinamycs of Savalai Hairtail fish (Lepturacanthus savala) in Sunda Strait Waters) - Siska Agustina; Menofatria Boer; Achmad Fahrudin (Bogor Agricultural University, 2015)
ABSTRACTSavalai hairtailis one of demersal fish that landed in PPP Labuan Banten with a fishing ground from the Sunda Strait waters. Savalaihairtail fish were caught by many gears (multigear) such as trawl, purse seine, small bottom trawl, and gillnet. This research aimed at reviewing population dynamic of savalai hairtail in Sunda Strait waters. The results showed the value of the growth coefficient (k) for female and male were 0,30/month and 0,23/month respectively, with asimptotic length (Lâˆž) 710,41 mm for females and 856,52 mm for males. First length capture for females and males were 460,46 mm and 454,66 mm respectively. First length of maturity for female and male fish were 567,24 mm and 599,73 mm respectively. Natural mortality (M) for the female and male fish were 0,27/year and 0,22/year respectively. Total mortality (Z) for the female and male fish were 1,25/year and 1,60/year respectively. Based on the relationship between the values of M and Z, then the arrest of mortality (F) known for female and male fish were 0,97/years and 1,38/year respectively. The rate of exploitation for female and male fish were72% and 83% respectively. Based on the current rate exploitation, savalaihairtail fish exploitation has exceeded optimum exploited level (50%), so it indicated the savalaihairtail was overfishing. The value of Lc was smaller than Lm indicated savalaihairtail experienced growth overfishing.Keywords: growth overfishing, overfishing, savalai hairtail, Sunda Strait——-ABSTRAKIkan layur merupakan salah satu ikan demersal yang didaratkan di PPP Labuan Banten dengan fishing ground dari perairan Selat Sunda. Ikan layur ditangkap dengan banyak alat tangkap diantaranya alat tangkap payang, pukat cincin, pukat pantai, jaring arad, dan jaring insang. Tujuan dari penelitian ini adalah mengkaji dinamika populasi sumber daya ikan layur (Lepturachantus savala) di Perairan Selat Sunda. Hasil penelitian menunjukkan nilai keofisien pertumbuhan (k) ikan betina dan jantan berturut-turut 0,30/bulan dan 0,23/bulan, dengan panjang asimptotik (Lâˆž) 710,41 mm dan 856,52 mm. Panjang ikan pertama kali tertangka (Lc) untuk betina dan jantan berturut-turut sebesar 460,46 mm dan 454,66 cm. Panjang ikan layur pertama kali matang gonad (Lm) untuk betina sebesar 567,24 mm dan jantan sebesar 599,73 mm. Laju mortalitas alami (M)) untuk ikan betina sebesar 0,27/tahun dan ikan jantan sebesar 0,22/tahun. Mortalitas total (Z) untuk ikan betina sebesar 1,25/tahun dan ikan jantan sebesar 1,60/tahun. Berdasarkan hubungan antara nilai M dan Z, maka mortalitas penangkapan (F) diketahui untuk betina sebesar 0,97/tahun dan jantan sebesar 1.38/tahun. Laju ekploitasi ikan layur betina dan jantan berturut-turut sebesar 72% dan 83%. Berdasarkan nilai laju eksploitasi, pemanfaatan ikan layur telah melebihi pemanfaatan optimal (50%), sehingga di indikasikan mengalami tangkap lebih. Nilai Lc<Lm menunjukkan tangkap lebih yang terjadi adalah growth overfishing.Kata kunci: growth overfishing, tangkap lebih, ikan layur, Selat Sunda